SEMANTIC FEATURES OF ASTRAL MYTHOLOGICAL UNITS IN ENGLISH AND KARAKALPAK - Usenova, V.J. (SCIENCE and SOCIETY, 2026)
This article examines the semantic features of astral mythological units based on definitional analysis within the framework of cognitive linguistics and linguocultural studies.